Analisis Risiko, Pengembalian, dan Koefisien Variasi Investasi Hijau pada Sektor Pertambangan - Amelia Lestari; Siti Komariah Hildayanti; Emilda Emilda (Value: Jurnal Manajemen dan Akuntansi)
In recent years, climate change has become a major issue around the world that affects various sectors. Human activities, such as the use of coal, petroleum, and natural gas,  contribute to the acceleration of global warming. The green economy has emerged as a new paradigm oriented towards environmental sustainability, one of which is through the SRI-KEHATI index which refers to the Sustainable Development Goal (SDGS) target No.15, which aims to protect, restore, and promote sustainable land use, as well as prevent biodiversity loss. This study aims to analyze the differences in risk, return, and coefficient of variation of green investment in SRIKEHATI-indexed and non-indexed mining sector companies during the 2019-2023 period. The research population includes 10 mining companies engaged in the metal and mineral industry on the Indonesia Stock Exchange (IDX), with a sample of 6 companies selected using purposive sampling. The study uses a quantitative method with monthly stock closing price data obtained from Yahoo Finance. The Independent Sample t-test statistical test is used to analyze the difference in risk and coefficient of variation, while the Mann-Whitney Test  is used to analyze the difference in return. The findings of the study show that there is no significant difference in risk, return, or coefficient of variation between SRI-KEHATI indexed and non-indexed companies.